Narrative abilities of preschool bilingual Norwegian-Russian children. (October 2017) - Rodina, Yulia
Aim and objectives/purpose/research questions: The study aims at conducting a comprehensive examination of the initial stages of narrative development in both languages of typically developing Norwegian-Russian simultaneous bilinguals. The objective of the study was to investigate whether narrative structure (macrostructure) and narrative productivity (microstructure) are language-dependent abilities (cf. The Linguistic Interdependence Hypothesis) and to explore language exposure effects on the narrative composites. Design/methodology/approach: The Multilingual Assessment Instrument for Narratives was used to assess narrative comprehension and production in preschool Norwegian-Russian children ( N = 16, M = 4;6) as well as in Norwegian- ( N = 16, M = 4;5) and Russian monolinguals ( N = 16, M = 4;5). Data and analysis: Multiple regression and correlation analysis was conducted to establish the relationship between the narrative macro- and microstructure in bilinguals and through the bilingual–monolingual comparison. In addition, more detailed quantitative and qualitative analysis at each level was performed. Individual bilingual children's data were also considered. Findings/conclusions: Overall the comparison of the narrative macro- and microstructure in the two languages of bilinguals supports the Linguistic Interdependence Hypothesis. Norwegian-Russian children's ability to compose and especially understand a story is equally developed in both languages. Exposure effects revealing the superiority of Norwegian, the majority language, are found primarily for microstructure measures. The complete picture is achieved through the bilingual–monolingual comparison, which suggests that narrative abilities in the minority language are sensitive to the amount of exposure and their acquisition can be vulnerable. Originality and significance/implications: The study provides new evidence on bilinguals' narrative abilities in a previously unstudied language combination. The new evidence contributes to better understanding of the initial stages of narrative development in typically developing simultaneous bilinguals and establishing the norms for the relevant abilities. Importantly, the study highlights the importance of examining language data in both languages of a bilingual child.